Biodegradation of Aromatic and Alkanes Compounds in Contamination Soils with Gasoline by Klebsiella pneumoniae - Al-Hadi Neif, Raad Abd; Abbas Al-Mayaly, Ithar Kamil (Iraqi Journal of Science, 2023)
This study investigated the potential of bacterial culture in bioremediation of gasoline pollutant soils. Klebsiella pneumoniae has shown a tremendous ability in bioremediation of gasoline. K.pneumoniae was isolated from three electrical generator pollutant soils with gasoline in different regions from Baghdad (Abu-Graib, Al-Khadra quarter and Al-Seleikh region. Bacteria was isolated and identified according to biochemical tests, with optimum temperature at 35°C and pH=5.FTIR spectrum was tested the ability of the K.pneumoniae to biodegrade the gasoline according to the peak areas, which appeared and referred to degrade amino compounds at wave number 3000 cm-1 (2955.23, 2923.47) which refer to the C-H with amines compounds and decreasing at wave number 1500cm-11458.77 and 1377.26 also appeared more degraded at regions of 3000 cm-1 (2955.31, 2922.97 and 2853.79) which represent alkanes C-H and amine groups.